ECOLOGICAL AND EDUCATIONAL SIGNIFICANCE OF THE FORMATION OF RESPONSIBILITY FOR NATURE IN YOUTH - Koldosheva Dilso'z Sunnatovna (International Engineering Journal For Research & Development, 2020)
In the article: the philosophical, psychological, pedagogical, ecological and educational significance of the formation of a responsible